WORKSHOP "EXPLORE YOUR PASSION, BUILD YOUR IMAGINATION" USING AFTER EFFECT AND PAINT TOOL SAI - Sumliyah; Maratus Solikah; Ine Sri Hayati Wahyuni; Muhalizah; Nova Wahyuni; Nurul Iftiani Yastri; Suniah (Jurnal Abdisci, 2024)
Implementing Community Service activities, especially in the school environment of SMK Negeri 1 Kedawung, is a form of our concern for students to gain insight into the use of the After Effect and Paint Tool Sai Application. Referring to the decision of the head of the standards body, curriculum, and education assessment, the Ministry of Education and Technology, namely Number: 024/H/KR/2022 to recognize the concentration of vocational skills in the context of an independent curriculum. One of the changes in the name of the Vocational High School (SMK) department is Multimedia (MM) changed to Visual Communication Design (DKV). Visual Communication Design (DKV) is the first major after the change in the independent curriculum, and this department requires a lot of guidance, motivation, and direction for students. Based on the results of the observation, our group decided to hold an explore your passion build your imagination service with illustrators and animators who are one of the outstanding alumni of SMK Negeri 1 Kedawung to increase students' motivation to learn in the multimedia world. The activity in this service is in the form of an introduction workshop on the use of multimedia in making creative video animations using After Effect and SAI Paint Tool.